Patronage Buying Motives of Milkindo's Tourists - Cahyanti, Mega Mirasaputri; Anjaningrum, Widiya Dewi (Graduate School, Universitas Brawijaya, 2021)
Agritourism with the concept of animal husbandry has its own uniqueness as a tourist destination. Among Agritourism at Malang City, Indonesia, with the concept of animal husbandry, only Milkindo stated their place as integrated dairy farming for recreation and education. The purpose of this study was to determine the relationship of patronage buying motives consisting of tourist sites, tourist location atmosphere, facilities at tourist sites, price & service quality to the decision process of tourists visiting tourism of the Milkindo Integrated Dairy Farming Recreational and Educational Tours. One hundred Samples were selected on a non-probability sampling with an accidental sampling approach. Quantitative Data is analysed by Partial Least Square (PLS) analysis. The result of this study is shown that facilities at tourist sites is the one variable that has a significant positively effect on the decision process of tourists visiting tourist sites, while the tourist location, tourist location atmosphere, and service quality don't have significant effect on it, meanwhile price has a negative but not significant effect. The findings show that the theory of motive theory of tourist's patronage buying motive toward Milkindo can be used as a basis for assessing attractions other than agritourism. In addition, it can be translated with different geographical and demographic conditions, because the study is only in the city of Malang, Indonesia. Keywords: Agritourism with Farming Concept, Patronage Buying Motives, Tourist Visiting Behaviour.